Towards the 42nd igip international symposium on engineering education in Kazan in 2013 - M. . Auer; V. . Prikhodko (Высшее образование в России)
The paper describes the activities of the International society for engineering education IGIP and its Russian monitoring committee (RMK). Further on, the paper deals with the activities of the Centers of engineering pedagogy founded under the initiative of RMK IGIP in a number of Russian technical universities for the purpose of providing pedagogical,psychological and vocational training for the university faculty and other categories of students.